Issues and challenges of senior citizens, analytical study from Sunnahic perspective - Fadhli, Ahmad Syarief; Fatah Yasin, Raudlotul Firdaus (Kolej Universiti Islam Perlis (KUIPs), 2020)
There is no denying the fact that every human who lived long, will reach a certain point of being weak and feeble, with all physical & mental attributes weakens. No matter how hard they try to discover methods to extend their lifetime, it is still inevitable. Allah stresses this fact of life cycle briefly in the Qur'an, such predetermined cycle contributes to various pattern of social interaction with the senior citizens. As he world advances in technology and modernity, men seem to disregard their preparation in handling this stage of life.